Effect of crab size and habitat type on the locomotory activity of juvenile shore crabs, Carcinus maenas - Almeida, M. J.
Post-settlement processes are a major focus in the study of the dynamics of marine populations and communities. Post-settlement movement of juveniles is an important, but often ignored, process which affects local predator–prey and competitive interactions. We used benthic suction sampling and pitfall traps to examine density and locomotory activity of Carcinus maenas juveniles in different intertidal habitat types in the Rio Mira Estuary, Portugal, to better understand intra-specific interactions in a system where density-dependent processes are known to regulate population dynamics. As expected, significantly higher densities of juvenile shore crabs were found from bare mud compared to densely vegetated habitats. At the time of sampling, small and intermediate stages together outnumbered by far the larger juveniles. Conversely, larger crabs were much more frequent than smaller ones in traps. A locomotory index (LI), i.e. the ratio between crab catch in pitfall traps and their density within their moving range, is proposed as a measure of movement. LI analyses indicated that: (1) movement is an order of magnitude higher in large than small juveniles and much higher in sparse than dense vegetation cover; (2) activity of small juveniles is mostly crepuscular, regardless of vegetation cover; and (3) movement of large juveniles is very limited in dense Zostera patches, but very high in sparsely vegetated areas, during the day and night. These results suggest that small juveniles are relatively protected under dense vegetation cover due to lower mobility of larger crabs, and provide evidence of temporal segregation of activity windows between juvenile crabs of different sizes, which may be a key mechanism to reduce cannibalism and therefore increase the carrying capacity of nursery habitats.